Seals used as "research assistants" in the polar oceans - Kovacs, Kit M; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Intraspecific differences in the diet of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Bester, Marthán; Kirkman, Stephen; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2010)
Intraspecific differences in the diets of many species of pinnipeds are to be expected in view of the great differences in morphology, life history and foraging behaviour between the sexes of many species. We examined the diet of the Antarctic fur seal population at Bouvetoya, Southern Ocean, to assess intersexual differences. This was made possible by the analysis of prey remains extracted from scats and regurgitations collected in areas used primarily by one or the other sex. The results indicate that both males and females feed primarily on Antarctic krill Euphausia superba with several species of fish and squid being taken, likely opportunistically given their prevalence. Significant differences were identified in the frequency of occurrence of otoliths in scats and the percentage numerical abundance of the major fish prey species in the diet. Adult males ate a smaller quantity of fish overall, but ate significantly more of the larger fish species. The greater diving capabilities of males and the fact that they are not limited in the extent of their foraging area by having to return regularly to feed dependant offspring may play a role in the differences found between the diets of males and females. Additionally, females might be more selective, favouring myctophids because they are richer in energy than krill. The absence of major differences in the diet between the sexes at this location is likely due to the high overall abundance of prey at Bouvetoya.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; sjøpattedyr

Pinniped and seabird research at Bouvetøya, 2000/01 : final contract report for the Norwegian Polar Institute - Hofmeyr, Greg; Bester, Marthán (Universty of Pretoria, 2002)
Keywords: Bouvetøya; ekspedisjoner; fugler; pelsseler; pinnipedier; seler; zoologi

Pinniped research at Bouvetøya, 2001/02 : final contract report for the Norwegian Polar Institute - Hofmeyr, Greg; Bester, Marthán (Universty of Pretoria, 2002)
Keywords: Bouvetøya; ekspedisjoner; pelsseler; pinnipedier; seler; zoologi

Bouvetøya pinniped monitoring programme: December 1998 - February 1999: final contract report for the Norwegian Polar Institute - Kirkman, Stephen; Bester, Marthán ([Universty of Pretoria], 2002)
Keywords: Bouvetøya; ekspedisjoner; pelsseler; pinnipedier; seler; zoologi

Mumifiserte seler fra Dronning Maud Land, Antarktis - Gjertz, Ian; Wiig, Øystein (Fauna, 2001)
Keywords: Dronning Maud Land; dyr; seler; zoologi

Prey of Antarctic fur seals at Bouvetøya, Southern Ocean - Klages, Norbert; Hofmeyr, Greg; Gjertz, Ian (Polar Record, 1999)
Publisher: Cambridge University Press
Keywords: Bouvetøya; pelsseler; pinnipedier; seler; zoologi

Digestibility of krill (Euphausia superba and Thysanoessa sp.) in minke whales (Balaenoptera acutorostrata) and crabeater seals (Lobodon carcinophagus) - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (British Journal of Nutrition, 1994)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

Digestibility of krill in crabeater seals and minke whales - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (1993)
Pages: 73 Publication Title: 10th Biennial Conference on the Biology of Marine Mammals Place: Galveston, Texas, USA
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

Satellite tracking of crabeater seals off Queen Maud Land in Antarctica - Nordøy, Erling S; Folkow, Lars P; Blix, Arnoldus Schytte (1993)
Pages: 81 Publication Title: 10th Biennial Conference on the Biology of Marine Mammals Place: Galveston, Texas, USA
Keywords: Dronning Maud Land; satellitt; seler; telemetri; zoologi

Biota of the antarctic pack ice: R/V Hero cruise 77-5 - Siniff, D.; Laws, R.; Oritsland, T.; Stirling, I.; Bengtson, J.; Demaster, D.; Reichle, R. (Antarctic Journal of the United States, 1978)
Between 22 October and 20 November 1977, we used National Science Foundation's R/v Hero to conduct studies of Antarctic seals in pack-ice areas of the Antarctic Peninsula. Our principal focus was on crabeater seals, but we also were interested in other pack-ice species, particularly leopard seals. Our work centered on (a) collecting female crabeater and leopard seals for reproductive material depicting various stages of the reproductive cycle, (b) documenting further the social structure and reproductive behavior of crabeater seals, (c) observing daily activity patterns and local movements of crabeater seals at fast-ice concentrations, and (d) investigating crabeater seal behavior at weaning and their interaction with leopard seals.
Keywords: Antarktis; Sørishavet; marin biologi; seler

Food Consumption of Seals in the Antarctic Pack Ice - Øritsland, Torger (Smithsonian Institution, 1977)
Publication Title: Adaptations within antarctic ecosystems : proceedings of the third SCAR symposium on antarctic biology
Keywords: Antarktis; biologi; dyreliv; havis; seler; sjøis; zoologi

Energetic significance of absorption of solar radiation in polar homeotherms - Øritsland, Nils Are (Antarctic ecology, 1970)
Keywords: Antarktis; fysiologi; seler; stråling; zoofysiologi

Biology and population dynamics of Antarctic seals - Øritsland, Torger (Antarctic ecology, 1970)
Keywords: Sørishavet; biologi; forskning; marinbiologi; seler; zoologi

Norwegian pelagic sealing reconnaissance in the Scotia Sea, 1964 - Øritsland, Torger (Polar Record, 1970)
Publisher: Cambridge University Press
Keywords: Sørishavet; biologi; ekspedisjoner; forskning; marinbiologi; seler; zoologi

Sealing and seal research in the south-west Atlantic pack ice, Sept.-Oct. 1964 - Øritsland, Torger (Antarctic ecology, 1970)
Keywords: MV Polarhav; Sørishavet; biologi; ekspedisjoner; forskning; marinbiologi; seler; zoologi

Estimates of local seal populations in the Antarctic, 1930/37 - Mackintosh, N A (Norsk hvalfangst-tidende, 1967)
Keywords: Sørishavet; seler; zoologi

Ynglende pelssel på Syd-Orknøyene = Fur seals breeding in the South Orkney Islands - Øritsland, Torger (Norsk hvalfangst-tidende, 1960)
Keywords: Sørishavet; pattedyr; seler; zoologi

A survey of the eared seals (family Otariidae) with remarks on the antarctic seals collected by M/K "Norvegia" in 1928-1929 - Sivertsen, Erling (Dybwad, 1954)
Publication Title: Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq., instituted and financed by consul Lars Christensen
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjonen; pattedyr; seler; sjøpattedyr; zoologi

Extracts from the Private Diary of the Late Nicolai Hanson - Hanson, Nicolai (Report on the collections of natural history made in the Antarctic regions during the voyage of the "Southern Cross", 1902)
Keywords: Antarktis; Kapp Adare; Rosshavet; Southern Cross; ekspedisjonen; ekspedisjoner; fauna; flora; fugler; oppdagelsesreiser; overvintring; seler; zoologi